Pengaruh Model Problem Based Learning Berbantuan Media Augmented Reality terhadap Kemampuan Pemahaman Konsep Bangun Ruang Siswa Kelas V di SDN 27 Cakranegara - Raudatul Jannah; Radiusman; Hikmah Ramdhani Putri (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to determine the effect of the Problem Based Learning (PBL) model assisted by Augmented Reality (AR) media on fifth-grade students’ understanding of geometric solid concepts at SDN 27 Cakranegara. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The research population consisted of 43 fifth-grade students divided into an experimental class and a control class. Data collection techniques included observation and essay tests administered during the pretest and posttest. Data analysis was conducted through normality testing, homogeneity testing, and hypothesis testing using an independent sample t-test. The findings revealed that the experimental class obtained a higher posttest mean score (68.91) compared to the control class (55.60). The hypothesis test results indicated a significance value of 0.009 < 0.05 and a calculated t value of 2.729 > t table of 2.013, indicating that H₀ was rejected and Hₐ was accepted. Therefore, it can be concluded that the implementation of the PBL model assisted by AR media had a significant effect on students’ understanding of geometric solid concepts. The use of AR media also enhanced students’ activeness, enthusiasm, and engagement during the learning process.